The relationship between preferred coaches’ leadership styles and stress levels among Chinese college bridge athletes - Wu, Ziwei; Zhang, Nan; Pan, Jiang; Chen, Yiqun; Han, Meijun; Soni, Nopembri; Shahril, Mohd Izwan; Mohd Nor, Mohad Anizu (Faculty of Sports Science and Recreation, 2024)
Bridge is an intellectual sport that helps to develop the ability to analyze logic and teamwork, and it is well developed in Chinese colleges. It was found that the leadership styles of Chinese college bridge coaches and the self-perceived stress of athletes have received less attention from scholars. This study aimed to explore the leadership styles of Chinese college bridge coaches, the selfperceived stress level of college bridge athletes, and the relationship between these two factors. This study contributes to the alleviation of self-perceived stress in college bridge athletes and to help college bridge coaches relieve the stress of bridge athletes. The research design for this study was quantitative. Respondents were athletes competing in the 2023 Chinese Collegiate Bridge Championships (N=210). The coaches’ Leadership Style Scale and Perception Stress Scale (Chinese 14-item, PSS) were used as the survey tools for this research. The data were analyzed by SPSS 26.0 software for extreme values, extreme minima, mean, standard deviation, and Pearson correlation. It was found that there are more democratic leadership styles (M = 4.18 ± 0.88) and less authoritarian leadership styles (M = 1.40 ± 0.59) among college bridge coaches. In the analysis of the stress data, most collegiate bridge athletes had low to moderate levels of self-perceived stress (M=21.77 ± 7.28), and only 17.1% had high levels of stress. In the correlation analysis between the two, self-perceived stress scores were significantly negatively correlated with the democratic leadership style (r = -0.193, p < 0.01), indicating that the democratic coaching style can dramatically reduce the self-perceived stress of bridge athletes. There is no significant correlation between self-perceived stress scores and authoritarian leadership styles.